Baltic Botanic Gardens: Tourist Guide - (:unkn) unknown (Latvijas Universitātes Botāniskais darzs, 2009)
The edition contains information about nine botanical gardens of Latvia, Lithuania and Estonia.These are places where to see the world's plant diversity, to become acquainted with threatened plants, gardening and to relax in nature's lap. Practical guide of the botanical gardens are provided.
Keywords: Research Subject Categories::NATURAL SCIENCES::Biology; Tallin botanic garden; Botanical garden of University of Tartu; Botanical garden of University of Latvia; National botanic garden of Latvia; Botanic garden of Vilnius University; Botanical garden of Klaipeda University; Šiauliai University Botanical garden